2020
DOI: 10.20546/ijcmas.2020.911.418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Land Use Systems on Major Nutrient Status in Soils of Westernghat-Chikamagalur, Karnataka, India

Abstract: The present study was conducted to assess the impact of different land-use systems on major nutrient status viz: Nitrogen, Phosphorus and Potassium in soils of central part of Western ghat, Karnataka. The land use types include both manmade systems (Agriculture: paddy; Horticulture: coffee, are canut, tea and banana); forest plantation (accacia and teak) and natural systems (Evergreen, semi-evergreen and grassland). In each land use systems, samples were collected from two depths (0-15 cm and 15-30 cm) at 20 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…The amount so ixed along N derived from mineralization might be suf icient to replace the N removed through the litter. These results are in accordance with Shivakumar et al (2020) who reported that higher available N content under natural systems namely evergreen and semievergreen compared to forest plantation systems viz., teak and acacia might be attributed to the variation in quality and quantity of litter as it is derived from mixed vegetation type under natural system. Further, the removal of vegetation by livestock grazing and exposure of soil surface may impact on the surface runoff due to direct drop of rainfall under agricultural land use system, which can remove the animal and plant residues from the surface soil layer thereby causing nitrogen depletion.…”
Section: Available Nitrogensupporting
confidence: 92%
See 3 more Smart Citations
“…The amount so ixed along N derived from mineralization might be suf icient to replace the N removed through the litter. These results are in accordance with Shivakumar et al (2020) who reported that higher available N content under natural systems namely evergreen and semievergreen compared to forest plantation systems viz., teak and acacia might be attributed to the variation in quality and quantity of litter as it is derived from mixed vegetation type under natural system. Further, the removal of vegetation by livestock grazing and exposure of soil surface may impact on the surface runoff due to direct drop of rainfall under agricultural land use system, which can remove the animal and plant residues from the surface soil layer thereby causing nitrogen depletion.…”
Section: Available Nitrogensupporting
confidence: 92%
“…Similarly, Nigussie and Kissi (2012) (275.97 kg ha ) which may be attributed to the accumulation of more organic matter on the surface layer and its subsequent decomposition than the subsurface soil layer. These results are in conformity with the results obtained by Shivakumar (2020) explaining the presence of higher available nitrogen content in the surface layer than that of the subsurface layer of different LUSs. The contents of available nitrogen were strongly associated (r =0.875*) with soil organic carbon in all the depths and decreased consistently with increasing soil depth under all LUSs (Table 6).…”
Section: Available Nitrogensupporting
confidence: 92%
See 2 more Smart Citations
“…It is clear from Figure 4 that all the LUSs accumulated higher biomass owing to greater NPK‐rich leaf surface area which in turn deposited in the soil after fall down and thus releases more NPK in soil upon their mineralization. Shivakumar et al (2020) reported that forest LUS has a higher amount of available NPK than other LUSs. In the present study, a higher NPK level was recorded in the TBFLUS which might be attributed to the humification process that led to higher OC content along with the presence of leaf litter in the surface soil.…”
Section: Discussionmentioning
confidence: 99%